Assessment of metals contamination of soils in Ulaanbaatar, Mongolia - Batjargal, Tserennyam; Otgonjargal, Enktur; Baek, Kitae; Yang, Jung-Seok (ELSEVIER SCIENCE BV, 2010)
The purpose of this survey is to investigate the current status of metal pollution of the soil in Ulaanbaatar, the capital city of Mongolia. During the last decade, the city has been rapidly urbanized. Twenty-two soil samples were collected from different parts of the city and analyzed by aqua regia extraction. Generally, metal pollution was not a serious problem in the city and there was no significant evidence of infiltration of metal solutions into subsoil (at a depth of 30 cm). However, it was recently found that the arsenic(As) concentration in the soil was higher than the guideline value and the lead(Pb) content in some samples was higher than normal. The source of As pollution appears to be the coal combustion in three power plants in the city. The sources of the increase in Pb pollution might be the remarkable increase in the number of used vehicles and the increase in the use of leaded fuel in the last few years. To evaluate the leaching potential of heavy metals, sequential extraction was conducted. The quantity of the easily extractable fraction of metals was lower than that of the hardly extractable (residual) fraction. As a result, the leaching potential of heavy metals in Ulaanbaatar was found to be quite low. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: URBAN SOILS; HEAVY-METALS; POLLUTION; TOPSOILS; EXTRACTABILITY; SPECIATION; PATTERNS; JORDAN; DUST; CITY